Optical properties of the complexes of detonation nanodiamonds with an indotricarbocyanine dye - N. V. Belko; M. P. Samtsov; G. A. Gusakov; A. P. Lugovski; A. A. Lugovski; V. A. Parkhomenko; E. S. Voropay (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
A method to create complexes of detonation nanodiamonds with molecules of an indotricarbocyanine dye was developed. The process of complex formation was shown to depend on the nanodiamond annealing conditions. Nanodiamonds that were vacuum annealed at 750oC display the most effective interaction with the dye molecules. Formation of the complexes was studied with the aid of optical spectroscopy in the visible and infrared regions.